Rising Dispersion in Age at First Birth in Europe: Is it related to Fertility Postponement? - Dimiter Philipov (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
This paper examines the dispersion of fertility across age and time which has rarely been studied. Using data from the Human Fertility Database, we examine fertility age schedules by looking at standard deviations in age at first births in European countries at different stages of fertility postponement. The standard deviation at first birth remained overall constant during the start of fertility postponement in the early 1970s, then it increased during the second stage marking the progression of postponement. It remained again constant at a higher level during recent years. The paper discusses the structural changes that might have caused these changes.
Keywords: 300; Variance in fertility schedules; standard deviation of fertility; variance and stages in fertility postponement; fertility schedules